Vascular Tone and Neurovascular Coupling: Considerations Toward an Improved In Vitro Model - Filosa, Jessica (Frontiers in Neuroenergetics, 2010)
In recent years, neurovascular research has made significant strides towards understanding how the brain neurovascular unit accomplishes rapid and spatial increases in blood flow following neuronal activation. Among the experimental models used, the in vitro brain slice preparation provides unique information revealing the potential signals and cellular mechanisms involved in functional hyperemia. The most crucial limitation of this model, however, is the lack of intraluminal pressure and flow in the vessels being studied. Moreover, differences in basal vascular tone have lead to varied interpretations regarding the polarity of vascular responses following neuron-to-glial stimulation. This dichotomy raises the important question: what is the role of vascular tone in neurovascular coupling? Given the complexity of astrocyte-induced neurovascular responses, we propose the use of a modified in vitro brain slice preparation, where intraluminal arteriolar pressure and flow are retained. Incorporation of these important hemodynamic variables will better simulate in vivo physiological conditions, while also influencing the modality of neuronal-glial excitability and vascular dynamics. Albeit its limitations, the in vitro brain slice preparation technique remains an ideal model to simultaneously monitor all of the functional constituents of the neurovascular unit, using electrophysiological and imaging techniques. Throughout this review, we discuss the advantages and disadvantages to be considered when using brain slices for neurovascular studies. Furthermore, I propose potential ways to overcome the current limitations. With the improvements proposed, I would argue that in vitro brain slice preparation can continue to facilitate novel studies of neurovascular coupling, with promise to yield exciting new insights into unique modalities of neuron-glial interactions in the regulation of neurovascular function.